The Role and Significance of the Concepts of Hard Skill and Soft Skill in Teaching It and Programming Languages - M.M.Ashurova; M.U. Ashurov (Zien Journals, 2023)
This article about hard skill and soft skill which are integral concepts during the lesson and work places. Both of them give to students to improve logical thinking and communication
Keywords: hard skill; soft skill; sql; algorithms